Mistrovství světa ve fotbale 2014 v kontextu tržní hodnoty týmů a jejich umístění - Šíma, Jan; Omcirk, Vilém; Ruda, Tomáš (Česká kinantropologie, 2015)
The content of the article specifies the dependence of football representations' market value participating in FIFA WORLD CUP 2014 on their results achieved at the Championship. A size of the team market value is fixed by the total sum of all players' market value without reference to their participation in the match. It is in view of their final result at the Championship, which is stated by the total sum of points obtained. From the results of regression and correlation analysis we can see a medium influence of team market value on the final result at the Championship 2014.The value of the correlation coefficient is 0.53. The nearest to the prediction of the obtained points is Uruguayan representation, with the value of y = 6.15, which is nearly similar to factual 6 won points. The farthest from the regression line is the successful representation of the Netherlands and, on the contrary, the unsuccessful representation of Spain. The partial goal was to state effectiveness of the national football teams at the Championship 2014 as a ratio between the quality of the representation (stated by the total team market value) and the sum of the points won at the Championship. From this point of view the Costa Rican team was the most successful. One Costa Rican point is represented by the sum of 2.96 million EUR, which is the least from the all national teams. The worst result was achieved by England, which won only one point. Its total market value of 334 million EUR represents the coefficient of its effectiveness as
Keywords: fotbal; dospělí; efektivita organizační; Soccer; Humans; Athletic Performance; lidé; socioekonomické faktory; mužské pohlaví; Male; Efficiency, Organizational; Socioeconomic Factors; Adult; sportovní výkon